Thermal enhancement of targeted cooling thermosyphon array applied to the embankment–bridge transition section of the Qinghai–Tibet Railway in warm permafrost - Kun Chen; Guo-Yu Li; Qi-Hao Yu; Yan-Hui You; Ming-Yang Jin; Jin-Xin Lu; Yao-Jun Zhao (Advances in Climate Change Research)
Permafrost degradation in the embankment–bridge transition section (EBTS) along the Qinghai–Tibet Railway has led to extensive damage to bridge structures, posing a serious threat to railway safety. With the ongoing global warming, reinforcing the affected EBTS to ensure long-term stability remains a pressing challenge. To address this issue, this study proposes a targeted cooling thermosyphon array (TCTA) approach utilising variable inclination evaporator (VIE) thermosyphons. The effectiveness of the VIE thermosyphon was evaluated through an in-situ test. Meanwhile, a three-dimensional numerical model was employed to analyse the overall cooling effect, long-term performance and thermal enhancement provided by the TCTA approach. The findings indicated that the VIE thermosyphon exhibited excellent cooling performance and maintained uniform wall temperature, with the lowest wall temperature reaching −15 °C. Within one year of implementation, a cold core of −2 °C formed at the centre of the foundation, and the permafrost table was uplifted by approximately 3 m, showcasing its potential to rapidly enhance the thermal stability of in-service EBTS in permafrost. With prolonged operation, the cold accumulative effect of this approach gradually becomes apparent, and the range of the low-temperature cores expands. This method effectively reinforces the thermal stability of in-service EBTS and is well-suited for future railway construction in warm permafrost amidst the challenges of climate change.